2003
DOI: 10.1080/09540090310001655101
|View full text |Cite
|
Sign up to set email alerts
|

A constructive model for the development of joint attention

Abstract: This paper presents a constructive model by which a robot acquires the ability of joint attention with a human caregiver based on its embedded mechanisms of visual attention and learning with self-evaluation. The former is to look at a salient object in the robot's view, and the latter is to learn sensorimotor co-ordination when visual attention has succeeded. Since the success of visual attention does not always correspond to the success of joint attention, the robot has incorrect learning data for joint atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(93 citation statements)
references
References 13 publications
4
78
0
10
Order By: Relevance
“…Here, we don't solve the question of joint attention which is an social referencing skill. Joint attention may also be reached using a learning protocol similar to Nagai [18] (developmental model for the joint attention). We think this approach can provide new interesting insights about how humans can develop social referencing capabilities from sensorimotors dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we don't solve the question of joint attention which is an social referencing skill. Joint attention may also be reached using a learning protocol similar to Nagai [18] (developmental model for the joint attention). We think this approach can provide new interesting insights about how humans can develop social referencing capabilities from sensorimotors dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…It has been tested in the case of gaze following in the context of a human-robot interaction by Nagai et al [8] and found to be feasible. This hypothesis relies on the assumption that the correlation is sufficiently strong to be discovered in practice.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first experiment on pointing and pointing gesture recognition using two robots. Earlier robotic experiments focused on gaze and pointing gesture recognition between a human and a robot [8,9]. A computational model of reward-based emergence of gaze following was presented in Carlson and Triesch [10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of robotics researchers have pointed out that it may play an important role in enabling smooth communication between humans and robots [2], [3]. Synthetic studies have been also conducted to understand the underlying mechanisms of the development of joint attention [4], [5]. We can expect such studies to enable realizing adaptive robot to changes in an environment including humans as well as to help understanding of human development [6], [7].…”
Section: Introductionmentioning
confidence: 99%